CAUSES OF SCHOOL VIOLENCE AND POSSIBLE REMEDIAL MODELS - Otilia APOSTU (National Centre for Policy and Evaluation in Education, 2018)
School violence is a manifestation as old as the history of the school. The forms and the frequency of violent manifestation, the involvement of the school actors for the initiation of violent demonstrations, as well as the perception and tolerance of public opinion about the forms of violence and its actors are those that vary throughout time, giving them specificity and differentiated understanding. School violence includes various forms of manifestation, and to combat and prevent it, it is essential to raise awareness of the phenomenon of violence and its acceptance in the wider context of the determining causes. This study focuses on the causes of school violence directly correlated with the determinants (individual, socio-familial, school), analysed at three different levels of manifestation: violence between students, violence students - teachers, violence teachers - students. The study uses survey data that explores the phenomenon of school violence at the national level, from multiple perspectives. The analysis uses quantitative data obtained through questionnaire surveys addressed to pupils, principals, teachers, school counsellors, as well as qualitative data obtained by surveys by focus group interview, carried out with students, teachers and parents. The analyses relate the opinions, sometimes antagonistic, of the different school actors on the causes of school violence. The purpose of the study is not to determine the truth or importance of the causes of school violence identified by the school actors, but from these causes will be identified measures, strategies, policies that implementation will lead to a unitary view of school actors on the problem of school violence and the reduction and control of violent manifestations at school.